Designing a model of factors affecting career decision, career path and attitude towards marriage among students - Mahdinia, Nazanin; Pourabrahim, Taghi; Sedaghat, Mastooreh; Ahmadi Tahor Soltani, Mohsen (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Background and Aim: the challenges related to employment or in fact the issue of work and unemployment is not only one of the most important social issues of the day in the country, but considering the rate of population growth in the last two decades, it can be considered the most important. The social challenge of the next few decades. The aim of the research was to design a model of factors influencing career decision-making, career path and attitude towards marriage among students. Methods: The current research method is exploratory in terms of purpose, applied, and in terms of data type. The statistical population of the qualitative part of the research included academic experts who were selected as the sample size by using the purposeful snowball sampling method and the principle of theoretical saturation. Results: Path analysis, factor analysis and structural equation modeling were used to analyze the data. The results showed that the correlation matrix of the identified indicators is suitable for confirmatory factor analysis and the confirmatory factor analysis indicates the good fit of the model. Conclusion: in the evaluation of the internal validity of the designed model, according to the experts, it indicates that the model has the required validity and the average answers of the experts to each question are significantly higher than the average scores in each question.